Addressing the 'postcode lottery' in local resource allocation decisions: a framework for clinical commissioning groups. - Russell, J; Greenhalgh, P; Lewis, H; MacKenzie, I; Maskrey, N; Montgomery, J; O'Donnell, C (SAGE Publications, 2013)
The Health and Social Care Act 2012 abolishes primary care trusts (PCTs) in England and hands responsibility for decisions about allocation of local healthcare resources to newly established clinical commissioning groups (CCGs). The NHS Constitution emphasizes patients’ rights to expect these decisions to be made ‘rationally’.1 The National Prescribing Centre (NPC), now the Medicines and Prescribing Centre at the National Institute for Health and Clinical Excellence, has directed considerable effort in recent years at defining the parameters of rational decision-making, and supporting PCTs in improving their approaches to prioritization and resource allocation.2–5 A key driver for this activity has been the so-called ‘postcode lottery’ of local decision-making (whereby a patient in one geographical area may receive NHS funding for a particular drug or treatment while a patient with similar clinical needs in another area may not), and a requirement to ensure that local resource allocation decisions are able to withstand public challenge and judicial review.4 Responding to concerns that significant organizational learning will be lost with the abolition of PCTs, and that new clinical commissioners will lack the skills, expertise and experience to make resource allocation decisions that have public and legal legitimacy, the NPC, commissioned by the Department of Health, embarked on a systematic process to develop a national ‘competency framework’ resource for those involved in making difficult prioritization decisions at a local level. This paper reports on how the NPC competency framework was developed, and presents a potentially transferable methodology for advancing a competency framework to support individual and organizational learning and improvement.